The effect of fresh fruit bunches, market value and leverage towards the palm oil producing companies in Malaysia / Jovane Jestin @ Justine - Jestin @ Justine, Jovane (2018)
The aim of this study is to investigate and analyze the relationship between the Fresh Fruit Bunches, Market Value and leverage ratio towards the profitability of the palm oil producing companies in Malaysia during 2008-2017. About 10 companies were chosen for the data collection and the whole data were the secondary data which is obtained from Thomson Reuters Data Stream and also from the Annual Reports. This study adopts panel regression model to measure the relationship between the independent variable towards the dependent variable and also to test the hypotheses. The result of this study was revealed that the fresh fruit bunches yield has significant negative relationship while the market value and debt ratio has insignificant positive relationship towards the profitability of the palm oil producing companies in Malaysia.